Grain boundary segregation and intermetallic precipitation in coarsening resistant nanocrystalline aluminum alloys. (15th February 2019) - Devaraj, A.; Wang, W.; Vemuri, R.; Kovarik, L.; Jiang, X.; Bowden, M.; Trelewicz, J.R.; Mathaudhu, S.; Rohatgi, A.
Abstract: In-spite of all of the unique properties of nanocrystalline materials, they are notorious when it comes to their susceptibility to thermally induced grain coarsening, thus imposing an upper limit to their application temperature. In this study, we demonstrate a coupled Monte Carlo-molecular dynamics simulation-guided experimental approach of improving the resistance to thermally induced grain coarsening in light-weight nanocrystalline Al-Mg alloys. The structure, grain boundary segregation of Mg, and extent of grain coarsening of the Al-Mg alloys were characterized using plan view and cross-sectional scanning transmission electron microscopy and atom probe tomography. Coarsening resistance is attributed to a combination of thermodynamic stabilization of grain boundaries by controlled Mg segregation, and kinetic stabilization through pinning of the boundaries with nanoscale intermetallic precipitates. Thus, we highlight the opportunities in extending the upper limit of application temperature for nanocrystalline alloys by using a complementary thermodynamic and kinetic stabilization approach. Graphical abstract: Image 1